Assessing the Effectiveness of Monetary Policy of Central banks - G. G. Gospodarchuka; E. S. Zeleneva (Финансы: теория и практика)
Monitoring the effectiveness of the monetary policy of central banks is a crucial factor in the strategic management of the monetary sphere, not only at the national but also at the global level of the economy. Therefore, improving the methodological tools for this monitoring is of both scientific and practical interest, which determines the relevance of the research topic. The study aims to develop methodological tools to conduct a quantitative and qualitative assessment of the effectiveness of the monetary policy of central banks. The work uses a targeted approach to determining the effectiveness of the monetary policy, as well as methods of systemic-structural, comparative economic and GAP analysis. The empirical analysis of the effectiveness of the monetary policy in several countries for the period of 2014-2019 relies on the data of the World Bank and the Bank of Russia. The novelty of the study is in the targeted approach to the analysis and assessment of effectiveness. This approach is based on the specific features of strategic management of monetary circulation, which allows for a comprehensive objective assessment of the effectiveness regardless of the variety of strategic objectives of monetary policy and their development mechanisms in different countries. The study resulted in the methodology for quantitative assessment of monetary policy effectiveness and the criteria for qualitative evaluation of the analyzed effectiveness. The authors made conclusions regarding changes in the effectiveness of monetary policy in different countries, identified trends in the effectiveness of the monetary policy of the Bank of Russia, and revealed imbalances in its effectiveness at the level of federal districts. The results of the study confirmed the applicability and practical significance of the developed tools for analyzing and assessing the effectiveness of the monetary policy of central banks. By their means, international and national organizations will manage to identify best practices to implement monetary policy and recommend them for countries with low effectiveness of strategic management of monetary circulation.